Notion of the virtual derivative - Valiukevičius, G. (Nonlinear Analysis: Modelling and Control, 2011)
Formal graphical procedures to calculate function’s derivative are proposed. This can be applied to calculate expressions of geometric objects, construct approximate schemes in numerical analysis of solution of differential equation.